2017
DOI: 10.1111/acem.13180
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging Versus Ultrasound as the Initial Imaging Modality for Pediatric and Young Adult Patients With Suspected Appendicitis

Abstract: In the diagnosis of appendicitis, US-first imaging is more time-efficient and less costly than rapid MRI despite inconclusive studies after US imaging. Unless the process of obtaining a rapid MRI becomes more efficient and less expensive, US should be the first-line imaging modality for appendicitis in patients 2 to 30 years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…We identified 11 studies that assessed the cost-effectiveness of US in the evaluation of acute appendicitis [18][19][20][21][22][23][24][25][26][27][28]. The impetus to avoid radiation in the pediatric population has sparked substantial research interest in this area.…”
Section: Evaluation Of Pediatric Appendicitismentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 11 studies that assessed the cost-effectiveness of US in the evaluation of acute appendicitis [18][19][20][21][22][23][24][25][26][27][28]. The impetus to avoid radiation in the pediatric population has sparked substantial research interest in this area.…”
Section: Evaluation Of Pediatric Appendicitismentioning
confidence: 99%
“…Imler [25] 2017 A comparison of US or MRI first in the evaluation of young patients for appendicitis showed higher overall costs and longer ED length of stay in the MRI group 10 Kharbanda [26] 2018 A study across nine pediatric EDs showed that in the evaluation of acute abdominal pain, US first sites had 5.2% lower total costs of treatment than CT first sites 17…”
mentioning
confidence: 99%
“…Medical imaging plays an important role in patients who present with an atypical clinical presentation or a relatively low clinical probability of appendicitis. International differences exist in diagnostic imaging pathways for suspected appendicitis, with computed tomography (CT), ultrasound, and more recently, magnetic resonance imaging shown to be of use [3]. It is widely accepted that, in children, ultrasound should be the first-line imaging modality, as it avoids the radiation burden of CT [4].…”
Section: Introductionmentioning
confidence: 99%
“…28 MRI has the obvious benefit of avoiding radiation exposure, but the disadvantages of higher cost, less availability than CT and also MRI may not be tolerated in young children (especially under age 5). 29 Although, Feed and swaddle MRI is feasible without sedation up to 6 months of age. 30 Anecdotally, MRI usage has increased in the emergency setting in recent years, perhaps due to radiation concerns raised in campaigns such as "Image Gently" 31 and "As Low As Reasonably Achievable (ALARA)", 32 and perhaps with increase in the availability of the modality, but to date, only three single centre studies describing MRI utilization in paediatric EDs [33][34][35] have been published, and further evidence-based research is needed.…”
mentioning
confidence: 99%